Recent advances in stationary phases and understanding of retention in hydrophilic interaction chromatography. A review - Jandera, Pavel; Janás, Petr (Elsevier Science BV, 2017)
Hydrophilic interaction chromatography (HILIC) is a rapidly developing liquid chromatography mode suitable for separation of strongly or moderately polar samples on polar columns in highly organic mixed mobile phases. In the past five years many new types of columns appeared based on silica gel, organic polymers and other types of supports. The present work reviews the new additions to their family. Further, the progress in the understanding of theoretical principles of the HILIC mode, especially of the role of the mobile phase, and of the adsorbed water are addressed. The amount of adsorbed water strongly depends on the type of the polar column and may be used to distinguish between "conventional HILIC" and " aqueous normal phase chromatography (ANP)". Further, sample structural effects on the retention are treated in terms of the Linear Solvation Energy Relationship model adopted for partially ionized polar compounds. The impact of dual HILIC-reversed phase (RP) mechanism on a possible increase of the applications of some polar columns is discussed. Attention is paid also to the increasing role of the HILIC mode in various two-dimensional LC techniques and the related mobile phase compatibility problems.
Nedávné pokroky ve stacionárních fázích a porozumění retenci v chromatografii na hydrofilní interakci.
Keywords: interaction liquid-chromatography; aqueous normal-phase; monolithic capillary columns; porous graphitic carbon; mixed-mode chromatography; tandem mass-spectrometry; solvation energy relationships; flavone natural antioxidants; vodné normální fáze; monolitické kapilární kolony; porovitý grafit; tandemová hmotnostní spektrometrie; solvatační energie; flavonové přírodní antioxidanty; monolitické kolony na bázi organického polymeru; monolitické kolony na bázi silikagelu